FREQUENCY OF PRIMARY SOLID MALIGNANT NEOPLASMS IN BOTH SEXES, AS SEEN IN OUR PRACTICE - Ahmad, Zubair; Azad, Najamul Sahar; Yaqoob, Nausheen; Husain, Akhtar; Ahsan, Aamir; Khan, Ambreen Nasir; Ahmed, Rashida; Kayani, Naila; Pervez, Shahid; Hassan, Sheema H. (Journal of Ayub Medical College Abbottabad, 2007)
Background: To determine the frequency of various histologic types of primary solid malignant neoplasms in males and females, in our practice, in a large series of surgical biopsies. Methods : A retrospective study of 20,000 consecutive surgical biopsies in the section of Histopathology, Aga Khan University Hospital (AKU), Karachi, in 2004. Results: Squamous cell carcinoma of oral cavity was the commonest malignant neoplasm in males followed by diffuse Large B cell, Non-Hodgkin's lymphoma and Prostatic adenocarcinoma. In females, infiltrating Ductal carcinoma of the breast was overwhelmingly the commonest malignant neoplasm followed by Squamous cell carcinoma of the oral cavity and esophagus. Conclusion: Out of 20,000 biopsies, there were 4616 (23.08%) malignant neoplsms. Carcinoma of oral cavity is very common in our population in both sexes. Key Words: Malignant Neoplasm, Male, Female, Primary